Present Status of Pre-emptive Analgesic and Its Effects on Postoperative Pain Control (Bangladesh Journal of Child Health, 2010)
Pre-emptive analgesic is regularly practiced as a part of well defined protocol in most of the tertiary hospitals in developed countries. In our country most of the hospitals do not practice this. But few centers practice it irregularly without following any defined protocol. Keeping this in mind the present study was carried out to find the current practice of pre-emptive analgesic and its effects on postoperative pain control.It was a cross-sectional study for 2 years. Sample size was 90; with a mean age of 8.7 years. Patients were selected from the department of paediatric surgery of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh Institute of Child Health, Dhaka and Dhaka Medical College Hospital, Dhaka. Observation were made on pre-emptive analgesic practice regarding the agents used for analgesia, route of administration and time of administration in relation to surgery. Postoperative pain was measured on the first postoperative day by Visual Analogue Scale and was graded.Only 17 (18.9%) patients received pre-emptive analgesic. Among them 12 patients received local infiltration and 5 patients received caudal block. Mean value of pain score who received pre-emptive analgesic was 49.7mm on the first postoperative day and which was "moderate" grade of pain. Mean value of pain score who did not receive pre-emptive analgesic was 67.0mm on the first postoperative day and which was "moderate" grade of pain.Postoperative pain control was relatively better in those patients who received preemptive analgesic. But further study should be carried out with large number of patients in different centers by using different drugs to develop a protocol for effective postoperative analgesia. Key words: Present; pre-emptive analgesic; postoperative pain control. DOI: 10.3329/bjch.v32i1.6006 Bangladesh Journal of Child Health 2008; Vol.32(1): 6-9